2017
DOI: 10.1016/j.apsusc.2016.10.192
|View full text |Cite
|
Sign up to set email alerts
|

Size effect on the adsorption and dissociation of CO2 on Co nanoclusters

Abstract: Spin-polarized density functional theory calculations were carried out to study the adsorption and dissociation properties of CO2 on size-selected Co13, Co38 and Co55 nanoclusters. Based on genetic algorithm method, Co13, Co38 and Co55 nanoclusters were predicted as the most stable high-symmetry structures among these Con (n = 2 to 58) nanoclusters from the Gupta potential. For the adsorption of CO2, CO and O on size-selected Co13, Co38 and Co55 nanoclusters, the lowest adsorption strength is found for all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…The presence of preadsorbed oxygen was responsible for forming carbonates of different structures [87,93]. On most metal surfaces, CO 2 activation is highly surface orientated, pressure-and particle size-dependent [89,[94][95][96]. Yu et al [96] demonstrated through spin-polarized DFT calculations that adsorption and dissociation of CO 2 was dependent on the Co particle size.…”
Section: Co 2 Activation On Representative Pure Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of preadsorbed oxygen was responsible for forming carbonates of different structures [87,93]. On most metal surfaces, CO 2 activation is highly surface orientated, pressure-and particle size-dependent [89,[94][95][96]. Yu et al [96] demonstrated through spin-polarized DFT calculations that adsorption and dissociation of CO 2 was dependent on the Co particle size.…”
Section: Co 2 Activation On Representative Pure Metalsmentioning
confidence: 99%
“…On most metal surfaces, CO 2 activation is highly surface orientated, pressure-and particle size-dependent [89,[94][95][96]. Yu et al [96] demonstrated through spin-polarized DFT calculations that adsorption and dissociation of CO 2 was dependent on the Co particle size. They showed that Co 55 nanoclusters had the highest CO 2 dissociation activity in comparison to Cu-based materials have gained much attention in the CO 2 conversion process due to their wide applicability in the different conversion processes and low cost [12,97].…”
Section: Co 2 Activation On Representative Pure Metalsmentioning
confidence: 99%
“…The clusters shown an optimal oxygen binding at the low coordinated edge sites in spite of the presence of high coordinated threefold sites. It is also noteworthy that most of the computational studies which reported the monotonic activity increment with nanocluster size toward saturation limit have adapted metallic clusters with periodic increase in number of surface layers as seen for cluster stoichiometries like 38, 55, 147 for cuboctahedron geometry 57,58 . However, global optimization studies have predicted that these cluster sizes can have different minima or nearby lying isomers which breaks the evolutionary structural pattern of these clusters 59 .…”
Section: Unique Size Shape and Composition Dependent Activity Of Nanoclustersmentioning
confidence: 99%
“…It is also noteworthy that most of the computational studies which reported the monotonic activity increment with nanocluster size toward saturation limit have adapted metallic clusters with periodic increase in number of surface layers as seen for cluster stoichiometries like 38, 55, 147 for cuboctahedron geometry. 57,58 However, global optimization studies have predicted that these cluster sizes can have different minima or nearby lying isomers which breaks the evolutionary structural pattern of these clusters. 59 In addition, the competition between Eley-Rideal (E-R) and Langmuir-Hinshelwood (L-H) Pathways which differ in terms of the order of simultaneous interactions of adsorbates has a strong dependence on cluster size.…”
Section: Size Effectsmentioning
confidence: 99%
“…56 These varied outcomes show that the particle size be strategic to control CO 2 adsorption, moreover, there are experimental efforts connected to the optimization of catalytic activities through substrate particle size effects. [173][174][175] The interest to study such effects on the adsorption is not only due to the area per volume ratio and presence of low-coordinated atoms, compared to condensed phases, but also due to thermodynamic, electromagnetic and quantum effects that influence the properties of nanoparticles in the atomistic level. 19,176 The ability to control the type of CO 2 interaction would be valuable, especially for the aforementioned TM that do not stabilize chemisorbed CO 2 easily.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%